Strategy for Improving the Level of Community Health Through Rural Innovation Program (Case Studies in Center Bangka and Banyuwangi) - Andini Putri Titasari (Inovbook Publications, 2021)
The health sector is an important part and must be considered by the Government of Indonesia. The people who really need health are the people, both rural and urban. Public health is an indicator of the quality of human life which is strongly influenced by environmental conditions in an area. One sign of low environmental health is air pollution. Air pollution is defined as the presence of foreign materials or substances in the air which causes changes in the composition (composition) of the air from its normal state, which can cause several diseases such as respiratory diseases. Tuberculosis (TB) infection is a disease whose spread is influenced by environmental and behavioral factors. In addition, reduced levels of oxygen in the environment are also caused by air pollution. For that we need innovations that can improve environmental health so that people's welfare can increase. For this reason, a rural innovation program related to the health of rural communities, especially in the health of respiratory diseases, in this case is TB, was created, which can improve the quality of environmental health and also the welfare of the community. In addition, it also identifies the influence of innovative oxygen enhancement programs by planting trees in rural communities. This research was conducted to identify rural innovation programs related to rural public health, especially on respiratory disease health, and also to identify the effects of innovative oxygen enhancement programs by planting trees in rural environments. The method used in this research is descriptive qualitative method. As a result, there was an increase in the percentage of TB sufferers because of the Ketok Pintu Sekaput program. In addition, the Shodaqoh Oxygen program, which was carried out in villages in Banyuwangi Regency, succeeded in planting 7,444,764 trees in 2018. Suggestions for the future, it is better for the community to always practice clean and healthy living, and better prevent preventive and make tree planting programs. at the RW level so that they can provide seeds according to the needs of each area.